very basic algebra
posted by very basic algebra on .
I was told long ago way back when
that when you have something like this
-x = 7
you solve for x by doing the following
(-x = 7)-
x = -7
but now that I think about it
your not actually multiplying by negative one what is actually happening is this right???
(- x = 7)-^-1
to get the negative ones to cancel out to give you this
x = -^-1 7
or simplified as x = - 7
so my question is does the negative in the denomenator matter??? can you always just move it up or take the opposite of the whole thing even with somehting like this
- x = (7x + 5x^2 - 3)^-1 (6x + 7x^2 -2)
do you sovle this the same way
(- x = (7x + 5x^2 - 3)^-1 (6x + 7x^2 -2))-^-1
x = (-(7x + 5x^2 - 3))^-1 (6x + 7x^2 -2)
is that correct???
my teachers use to tell me that you could just multiply by negative one because it dosen't change its value but that is not true as it changes its direction
Your teachers are right. I do not comprehend your thinking. You are obfuscating a very simple operation, multiplying each side by -1